Lesson Plan Profile on Respiratory System Material with the TPACK Approach During the Pandemic Period at Senior High School Brebes Regency - Faqih Aziz; Atip Nurwahyunani (International Journal of Research in Education, 2023)
TPACK (Technological Pedagocical Content Knowledge) is about the importance of integration between technology and pedagogy in content development in education. This study aims to determine the lesson plan Profile for Respiratory System Material with the TPACK Approach in State Senior High Schools  Brebes Regency during the Pandemic Period. The subject in this study was the lesson plan for the respiratory system material for class XI in the even semester. The sampling technique used in this research is proportional stratified random sampling. This study uses instruments in the form of observation sheets and interview questionnaires. The results of this study indicate that lesson plan approaching TPACK compiled there are 3 components that are in the very good category, namely Content Knowledge (CK) with a percentage of 91.25%, Pedagogical Knowledge (PK) with a percentage of 90.83% and Pedagogical Content Knowledge (PCK) with a percentage of 81.25%. Components that are included in the good category have 1 component, namely Technological Knowledge (TK) with a percentage of 60.42%. Then there are 3 components that are in the sufficient category, namely the Technological Content Knowledge (TCK) component with a percentage of 51.67%, Technological Pedagogical Knowledge (TPK) with a percentage of 52.92% and component (TPACK) with a percentage of 48.33%. The lesson plan profile was included in the "good" category with an average percentage of 68.10%. It’s means that during pandemic period, the Biologi lesson plan for respiratory system material in senior high school Brebes Regency was made by TPACK approach.